Pengembangan Google Sites Sebagai Multimedia Pembelajaran E-Learning dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Akidah Akhlak Fase E - Muhammad Kholik; Erawadi Erawadi; Hamdan Hasibuan (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2025)
Learning Akidah Akhlak in Phase E at MAN 2 Padang Lawas faces challenges due to the lack of interactive learning media and students’ weak critical thinking skills. To address these issues, this study developed an e-learning medium based on Google Sites to support active and independent learning. The objective of the research is to create a learning medium that is valid, practical, and effective in enhancing students’ critical thinking abilities. The method used is Research and Development (R&D) employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were students of class X-1 at MAN 2 Padang Lawas. Data were collected through questionnaires, tests, expert validation, and documentation. The results indicate that the developed learning media is highly valid (average validation score above 89%), highly practical (88.17%), and effective in improving student learning outcomes (N-Gain score of 0.48; t-test shows significant improvement). This media is therefore suitable for use in Akidah Akhlak learning.